2023
DOI: 10.7150/thno.77694
|View full text |Cite
|
Sign up to set email alerts
|

Targeting WWP1 ameliorates cardiac ischemic injury by suppressing KLF15-ubiquitination mediated myocardial inflammation

Abstract: Rationale: Previous studies have suggested that myocardial inflammation plays a critical role after ischemic myocardial infarction (MI); however, the underlying mechanisms still need to be fully elucidated. WW domain-containing ubiquitin E3 ligase 1 (WWP1) is considered as an important therapeutic target for cardiovascular diseases due to its crucial function in non-ischemic cardiomyopathy, though it remains unknown whether targeting WWP1 can alleviate myocardial inflammation and ischemic injury post-MI. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Cumulative studies have demonstrated that the SCF E3 ubiquitin ligase family acts as an important regulator of post-translational modification and is closely associated with cardiovascular diseases such as cardiac hypertrophy, myocardial infarction, arrhythmia, and myocardiotoxicity [ 26 , 27 ]. For example, FBXL22 was identified as a cardiac-enriched F-box protein that modulates sarcomeric protein turnover and is critical for maintaining contractile function in vivo [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative studies have demonstrated that the SCF E3 ubiquitin ligase family acts as an important regulator of post-translational modification and is closely associated with cardiovascular diseases such as cardiac hypertrophy, myocardial infarction, arrhythmia, and myocardiotoxicity [ 26 , 27 ]. For example, FBXL22 was identified as a cardiac-enriched F-box protein that modulates sarcomeric protein turnover and is critical for maintaining contractile function in vivo [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies connect ischemic cardiomyopathy and specific congenital heart diseases to cell apoptosis [ 17 , 20 , 21 ]. The consequences of ischemia- and hypoxia-induced myocardial cell apoptosis are severe, leading to adverse cardiac outcomes such as ventricular remodeling [ 11 , 22 , 23 ]. The exact role of miR-182-5p in these apoptosis pathways remains ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that KLF15 is an upstream regulator of metabolic gene expression, and that it is negatively regulated by EZH2 (an epigenetic regulator) in a SET structural domain-dependent manner for cardiac metabolism and structural reprogramming ( 92 ). Additionally, KLF15 suppresses gene expression and negatively regulates adverse cardiac remodeling and hypertrophy in ICM progression ( 72 , 92 , 96 ). Specifically, KLF15 antagonizes the expression of various genes actively involved in cardiac remodeling.…”
Section: Klfs and Cardiomyopathymentioning
confidence: 99%